Influence of irrigation methods and fertilizer levels on productivity of potato (Solanum tuberosum) - SHARMA, VIPIN; SHARMA, I P; SPEHIA, R S; Kumar, Pardeep (The Indian Journal of Agricultural Sciences, 2012)
A experiment was laid in split-plot design and the treatments comprised sprinkler, drip and furrow irrigation as main plot along with three doses of fertilizers, viz F1 (NPK @ 150:150:125 kg/ha), F2 (NPK @ 125:125:100 kg/ha) and F3 (NPK @ 100:100:75 kg/ha) as sub-plot treatments. Results of the study indicated that irrigation methods manipulated the hydrothermal regimes of the soil comprehensively and mean maximum monthly temperature was lowered by about 1.2oC under sprinkler irrigation. Under drip irrigation, moisture was near to the field capacity throughout the growth period, whereas, in conventional furrow irrigation, the moisture status curve traveled from above field capacity to 50% moisture depletion conditions. The yield of tubers was appreciably higher under sprinkler and drip, compared to furrow irrigation method. F1 and F2 exhibited non significant differences among themselves, in respect of tuber yield, but were significantly higher than F3. Economic analysis indicated that sprinkler irrigation and F2 resulted in optimum benefit: cost ratio.